Field-based molecular detection of Batrachochytrium dendrobatidis in critically endangered Atelopus toads and aquatic habitats in Ecuador - Riascos-Flores, Lenin R. (2024)
Batrachochytrium dendrobatidis (Bd) is a lethal fungal species that parasitizes vertebrates and is associated with the worldwide decline of amphibian populations. The development of sensitive, rapid detection methods, particularly DNA-based techniques, is critical for effective management strategies. This study evaluates the efficacy of DNA extraction and a portable PCR device in a mountable field laboratory setup for detecting Bd near the habitats of three critically endangered Atelopus toad species in Ecuador. We collected skin swabs from Atelopus balios, A. nanay, and A. bomolochos, and environmental DNA (eDNA) samples from streams in Andean and coastal regions of Ecuador. For eDNA, a comparison was made with duplicates of the samples that were processed in the field and in a standard university laboratory. Our findings revealed Bd detection in eDNA and swabs from 6 of 12 water samples and 10 of 12 amphibian swab samples. The eDNA results obtained in the field laboratory were concordant with those obtained under campus laboratory conditions. These findings highlight the potential of field DNA-based monitoring techniques for detecting Bd in amphibian populations and their aquatic habitats, particularly in remote areas. Furthermore, this research aligns with the National Action Plan for the Conservation of Ecuadorian Amphibians and contributes to the global effort to control this invasive and deadly fungus